Relationship Between Age and the Incidence of Postoperative Hypertension - Pramono, Ardi; Sugiyarti, Chaerunnisa AP (Al Makki Health Informatics Journal, 2023)
Postoperative hypertension is a significant and transient increase in blood pressure that develops within the first 4 hours to 48 hours after a surgical procedure. These events are associated with increased sympathetic tone and vascular resistance. Hypertension is defined as a systolic blood pressure of 130 mmHg and/or a diastolic blood pressure of 80 mmHg. Postoperative hypertension can lead to complications of increased myocardial oxygen demand, cerebrovascular accident, and even death. This study aims to determine the effect of age on post-operative hypertension at PKU Muhammadiyah Gamping Hospital. This research is an analytical observational study using a cross sectional design and using the chi-square test to determine the relationship between age (p < 0.05) and the incidence of postoperative hypertension. The subjects of this study were 123 men who underwent mild to moderate elective surgery using general anesthesia. This study shows that there is a relationship between age and the incidence of hypertension after surgery with general anesthesia (p, 0.05). There were 67 subjects experiencing postoperative hypertension (54.5%) and the majority of subjects (66.66%) in the age range 46-80 years, had postoperative hypertension and the most minor incidence (29%) was in the age range 17-25 year.